Effect of Annealing and Etching Times on Anatase TiO2 Hollow Sphere - Rakhman, Khusna Arif; Aprilita, Nurul Hidayat; Kartini, Indriana (Molekul, 2023)
The development of high-efficiency photocatalysts plays an important role in the application of solar energy conversion. Titanium dioxide (TiO2) with an anatase crystalline phase is well-known as semiconductor thin layers for solar cells. This work has constructed a novel TiO2 hollow sphere (HST) in a 2-step synthesis. The first step is coating the SiO2 template with TiO2 to build a core-shell of SiO2@TiO2 (CSST). The second step is etching via sonication to elute the SiO2 from CSST and construct the HST. The annealing of CSST for 1 to 6 hours and etching for 1 to 7 hours has resulted in the HST with different crystallite sizes and microstrains. The HST of ~90 nm has been fabricated with crystallite size of 9.53 to 20.54 nm and microstrain from 0.34 to 3.42. It was found that the optimum crystallite size and microstrain of HST obtained via annealing the CSST for 2 hours and etching for 5 hours has the best photooxidation of I- under UV irradiation. The optimum crystallite size and microstrain of HST via annealing and etching times can be recommended for the future of solar cell fabrication and applications.